Perbandingan Persentase Risiko Meninggal pada Pasien Covid-19 Komorbid TBC dengan Komorbid Lainnya di Kabupaten Pati - Randi Eka Istananta; Teguh Budiharjo; Surati Surati (Jaringan Laboratorium Medis, 2023)
Corona Virus Disease 2019 (COVID-19) is a disease that has never previously been found in humans and is a new type of disease. The virus that causes COVID-19 is called Sars-CoV-2. It was found that patients experienced increased mortality due to COVID-19 because they had comorbid diseases. COVID-19 patients who have one comorbid disease are at risk of death up to 6.5 times higher than COVID-19 patients without comorbidities. Pulmonary TB is a comorbidity that can make a person more susceptible to contracting COVID-19 with severe symptoms. Apart from attacking the lungs, COVID-19 also damages the lungs. Damaged lungs prevent the body's organs from getting enough oxygen, which can trigger organ damage that can cause death. The aim of this study was to compare the percentage risk of death in COVID-19 patients who had comorbid TB disease with COVID-19 patients who had comorbid kidney disease and DM in the Pati area, Central Java. This research can be a reference for data regarding the percentage risk of death in COVID-19 patients with comorbidities. This research uses a descriptive, observational research design. The samples in this study were COVID-19 sufferers who had comorbid TB, comorbid kidney disease and comorbid DM. The sample population during the period January to December 2021 was 998. The sample was determined using the Slovin formula with a total of 135 samples with a sampling quota taken. Results Comorbid TB has a percentage risk of death of 40%, comorbid kidney has a percentage risk of death of 33.3%, and comorbid DM has a percentage risk of death of 6.8%. Comorbid TB is a comorbid that has the highest percentage risk of death, so intensive care is important for sufferers.